Enzymatic Stoichiometry and Microbial Resource Limitation in a Saline-Alkaline Soil Five Years After Biochar Application, Fertilization, and Irrigation - Jingjing Li; Yinku Liang; Lihua Xue; Wenwen Li; Sheng Zhang; Kazem Zamanian; Xiaoning Zhao (Agronomy)
The effect of biochar addition on enzyme stoichiometry and regulatory mechanisms in saline-alkali soil is still vague. We studied how five years (2018–2023) of applying 10 t biochar ha−1 yr−1 influences soil’s chemical and microbial properties, microbial element utilization efficiency, and resource limitations in the Tarim River basin. Low, medium, and high nitrogen fertilization (kg N ha−1) and irrigation (W) (mm) with or without biochar (B) were as follows: low nitrogen low irrigation (LNLW, 100/140), mid nitrogen mid irrigation (MNMW, 200/220), high nitrogen high irrigation (HNHW, 300/320), LNLWB, MNMWB, and HNHWB. Biochar application (LNLWB, MNMWB, HNHWB) increased soil organic carbon (+61%, +55%, +59%), total N (+9%, +16%, +8%), total phosphorus (+6%, +5%, +27%), microbial N (+75%, +86%, +28%) and P use efficiency (+60%, +45%, +27%), but decreased microbial biomass carbon (−6%, −29%, −45%), and microbial carbon use efficiency (−6%, −7%, −7%). Biochar application alleviated microbial C limitation but increased the P limitation of MNMW and the N limitation of HNHW. In conclusion, with a 1/3 reduction in N fertilization and irrigation compared with HNHW (MNMW), biochar can greatly alleviate microbial resource limitations and improve soil fertility in saline-alkaline soils.